2010
DOI: 10.1007/s00203-010-0646-9
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy is induced by the type III secretion system of Vibrio alginolyticus in several mammalian cell lines

Abstract: Vibrio alginolyticus is a gram-negative bacterium and has been recognized as an opportunistic pathogen in marine animals as well as humans. Here, we further characterized a cell death mechanism caused by this bacterium in several mammalian cell lines. The T3SS of V. alginolyticus killed HeLa cells by a very similar cell cytolysis mechanism in fish cells, as evidenced by cell rounding and LDH release; however, DNA fragmentation was not observed. Further studies showed that caspase-1 and caspase-3 were not activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…In V. alginolyticus, a V. harveyi-like QS signaling system has been characterized, which involved pivotal LuxO and LuxR regulators (16)(17)(18)(19)(20)(21)(22)29). AphA has been reported as another master regulator of QS in V. harveyi, V. cholerae, and V. parahaemolyticus (3,4,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In V. alginolyticus, a V. harveyi-like QS signaling system has been characterized, which involved pivotal LuxO and LuxR regulators (16)(17)(18)(19)(20)(21)(22)29). AphA has been reported as another master regulator of QS in V. harveyi, V. cholerae, and V. parahaemolyticus (3,4,34).…”
Section: Discussionmentioning
confidence: 99%
“…The major virulence factors of V. alginolyticus are extracellular proteases, motility, siderophore-dependent iron uptake systems, biofilm, type III secretion systems (T3SS), and type VI secretion systems (T6SS) (16)(17)(18)(19)(20)(21)(22). These factors and some other virulence-related genes are closely regulated by the QS system in V. alginolyticus.…”
mentioning
confidence: 99%
“…Among the vibrios, V. alginolyticus , V. harveyi and V. tubiashii possess T3SSs that are highly homologous to V. parahaemolyticus T3SS1 [8]. The V. alginolyticus T3SS exhibits cytotoxicity in mammalian and fish cells [33], [34]. Because VepA is also conserved among these species, it is possible that VepA homologs are involved in the cytotoxicity of other Vibrio species.…”
Section: Discussionmentioning
confidence: 99%
“…V. alginolyticus is prevalent in coastal waters of southern China and it is commonly associated with costly disease of aquatic animals (Austin, 2010). Previous studies demonstrated that V. alginolyticus induces apoptosis, cell rounding and osmotic lysis in fish cells and autophagy in mammalian cell lines in a T3SS-dependent manner (Zhao et al, 2010, 2011). Although the T3SS of V. alginolyticus is similar to T3SS1 of V. parahaemolyticus with respect to gene synteny (Zhao et al, 2010), it is unclear if the same regulatory mechanism is employed by V. alginolyticus .…”
Section: Introductionmentioning
confidence: 98%